Photometric Determination of vanadium(V) after Adsorption of its 1-Hydroxy-1-(o-Chlorophenyl)-3-Phenyl-2-Thiourea Complex of Microcrystalline Naphthalene - Mehra, Rita; Mathur, S.P. (Asian Journal of Chemistry, 2010)
A water insoluble stable complex of vanadium(V) with 1-hydroxy-1-(o-chlorophenyl)-3-phenyl-2-thiourea is separated from aqueous phase by its adsorption on microcrystalline naphthalene. The adsorbed complex is dissolved in dimethylformamide. The absorbance of the solution is measured at 395 nm. A linear relationship exists between absorbance and concentration of vanadium(V) in the concentration range of 4–110 μg of vandium in 10 mL of DMF. The molar absorptivity was found to be 3.46 x 104 l mol–1 cm–1 at 395 nm and sensitivity being 1.13 x 10–2 μg cm–2 of vanadium for the absorbance of 0.001.